2009
DOI: 10.1038/sj.bjc.6604871
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of temporal and generational trends in the incidence of anal and other HPV-related cancers in Southeast England

Abstract: Patients diagnosed in 1960 -2004 with cancer of the cervix, anus, vulva, vagina or penis were identified from the Thames Cancer Registry database, and age-standardised period (temporal) incidence rates calculated by direct standardisation. Age-cohort modelling techniques were used to estimate age-specific incidence rates in the earlier and later cohorts, enabling the calculation of agestandardised cohort (generational) rates. Incidence of anal cancer increased for both men and women over the period studied, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
57
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 33 publications
11
57
1
1
Order By: Relevance
“…5 In recent studies of women and men from the general population in Denmark in the age group 18-45 years, a high proportion of women (30%) and men (43%) reported having had more than 10 lifetime partners, 23,24 and surveys in Denmark and Scotland indicate that the prevalence of receptive anal intercourse tends to be higher in women than in men, which might be one of the explanations for the higher incidence of anal cancer in women. 20,25 Our finding that the incidence of anal cancer was increased particularly among younger people is in line with the report of Robinson et al, 21 who compared estimated agespecific incidence rates of anal cancer in different birth cohorts. They found that the incidence of anal cancer increased mainly in the cohorts born around 1940 and Epidemiology onwards.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…5 In recent studies of women and men from the general population in Denmark in the age group 18-45 years, a high proportion of women (30%) and men (43%) reported having had more than 10 lifetime partners, 23,24 and surveys in Denmark and Scotland indicate that the prevalence of receptive anal intercourse tends to be higher in women than in men, which might be one of the explanations for the higher incidence of anal cancer in women. 20,25 Our finding that the incidence of anal cancer was increased particularly among younger people is in line with the report of Robinson et al, 21 who compared estimated agespecific incidence rates of anal cancer in different birth cohorts. They found that the incidence of anal cancer increased mainly in the cohorts born around 1940 and Epidemiology onwards.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with reports from the USA of increases in incidence in periods between 1940 and 2003 3,4,[16][17][18][19] and from other European countries. [20][21][22] As in the 2 most recent European studies, we observed that the increase was particularly evident in women. 20,21 In Scotland, the incidence of squamous cell carcinoma in men tended to decrease or plateaued from the late 1990s onwards.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Ignoring the effects of age and birth cohort (data not shown), we obtained estimates for thyroid cancer incidence rates of 1.34 for men and 6.3 for women (per 100,000 inhabitants), which were, respectively, 13% and 16% higher than those obtained when polynomial models were used. Approaches that consider age and birth cohort effects also proved relevant in estimating incidence rates for cancers of the breast and lung, among others 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…The anal cancer diagnostic category bifurcates an overlap with more prevalent, less treatable rectal cancers. Anal cancer is uncommon, with an overall annual incidence of about 1 per 100,000 reported in England (Robinson, Coupland and Møller, 2009) and elsewhere. However, global incidence is increasing rapidly, probably through greater sexual transmission of the human papilloma virus (HPV) iii and immunodeficiency resulting from the spread of HIV and medical use of immunosuppresants (Ryan, Compton and Mayer, 2000).…”
Section: The Clinical Background: Anal Cancer and Its Treatmentmentioning
confidence: 99%